Recovery of Aging-Related Size Increase of Skin Epithelial Cells: In vivo Mouse and In vitro Human Study - Sokolov, Igor; Guz, Natali V.; Iyer, Swaminathan; Hewitt, Amy; Sokolov, Nina A.; Erlichman, Joseph S.; Woodworth, Craig D. (PLOS ONE, 2015)
The size increase of skin epithelial cells during aging is well-known. Here we demonstrate that treatment of aging cells with cytochalasin B substantially decreases cell size. This decrease was demonstrated on a mouse model and on human skin cells in vitro. Six nude mice were treated by topical application of cytochalasin B on skin of the dorsal left midsection for 140 days (the right side served as control for placebo treatment). An average decrease in cell size of 56±16% resulted. A reduction of cell size was also observed on primary human skin epithelial cells of different in vitro age (passages from 1 to 8). A cell strain obtained from a pool of 6 human subjects was treated with cytochalasin B in vitro for 12 hours. We observed a decrease in cell size that became statistically significant and reached 20–40% for cells of older passage (6–8 passages) whereas no substantial change was observed for younger cells. These results may be important for understanding the aging processes, and for cosmetic treatment of aging skin.